2008
DOI: 10.1177/00333549081230s206
|View full text |Cite
|
Sign up to set email alerts
|

Partnering to Meet Training Needs: A Communicable-Disease Continuing Education Course for Public Health Nurses in North Carolina

Abstract: to create a free continuing education course in communicable-disease surveillance and outbreak investigations for public health nurses. The course was a competency-based curriculum with 14 weeks of Internet-based instruction, culminating in a two-day classroom-based skills demonstration.In spring 2006, the course became mandatory for all public health nurses who spend at least three-fourths of their time on tasks related to communicable diseases. As of December 2006, 177 nurses specializing in communicable dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 5 publications
0
21
0
1
Order By: Relevance
“…We identified public health training programs delivered in over 11 countries: Australia, 10,16,17 Bolivia, 18 Brazil, 19 Canada, [20][21][22] Greece, 23 the Islamic Republic of Iran, 24 Mexico, 25 Rwanda, 26,27 Uganda, 28 the United Kingdom 29 and the United States of America (USA). [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] One program offered trainings in over 77 countries, 46 and another trained participants in Austria, Lithuania and the Netherlands. 9 Within the past 7 years, 19 of these articles were published.…”
Section: Public Health Training Program Characteristicsmentioning
confidence: 99%
“…We identified public health training programs delivered in over 11 countries: Australia, 10,16,17 Bolivia, 18 Brazil, 19 Canada, [20][21][22] Greece, 23 the Islamic Republic of Iran, 24 Mexico, 25 Rwanda, 26,27 Uganda, 28 the United Kingdom 29 and the United States of America (USA). [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] One program offered trainings in over 77 countries, 46 and another trained participants in Austria, Lithuania and the Netherlands. 9 Within the past 7 years, 19 of these articles were published.…”
Section: Public Health Training Program Characteristicsmentioning
confidence: 99%
“…Adults-whether public health graduate students, participants in experiential learning fellowships in public health, or public health professionals in continuing education courses-expect to apply the competencies achieved in their program to the workplace (2,60). If competency or the instructional experience is deemed irrelevant or ineffectual, adults will derive no professional benefit from the experience.…”
Section: Adult Learning Theorymentioning
confidence: 99%
“…Adult learning principles also implicitly or explicitly undergird the design of many continuing education courses designed for public health professionals (2,36,68). Although little has been formally documented regarding the use and effectiveness of adult learning principles in such programs and the impact of not using such principles, these programs have been highly successful in developing the future public health workforce (53,54,61,81).…”
Section: Adult Learning Theorymentioning
confidence: 99%
“…A hybrid continuing education course for public health nurses included online modules with a classroom session. Participants reported that the Internet-based lectures and classroom exercise improved their learning (Alexander et al, 2008). Emerging research shows that this approach produces relatively equal or better learning results compared with traditional classroom learning.…”
Section: Rationale For Hybrid Formatmentioning
confidence: 99%